Success with Microsoft Dynamics CRM 4.0 - Yetter, Aaron (Springer, 2017)
Success with Microsoft Dynamics CRM 4.0: Implementing Customer Relationship Management is aimed at readers who are interested in understanding how to successfully implement Microsoft Dynamics CRM 4.0 within their projects. It is intended as an implementation roadmap for the business and technical representatives leading or engaged in a project.